1991
DOI: 10.1099/00221287-137-5-1179
|View full text |Cite
|
Sign up to set email alerts
|

Separating the efflux and influx components of net nitrate uptake by Synechococcus R2 under steady-state conditions

Abstract: N isotopic discrimination was used to determine the ratio of influx to efflux in experiments in which NO: reduction was decreased (and also net NO; uptake, since under steady-state conditions, net NO? uptake is equal to the rate of reduction) by tungstate. Exponential growth rate constants for the cyanobacterium Synechococcus sp. R2 grown in media containing 0.18 pM-molybdate decreased linearly (0.040 to 0.013 h-l ) with increasing tungstate concentration (0 to 0.2 mM). Values of the overall, observed N isotop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that variations in cellularlevel isotope effect expression is imparted by changes to the ratio of cellular substrate uptake to efflux (Shearer et al 1991;Needoba et al 2004;Granger et al 2008). However, it has been shown in P. stutzeri that uptake and efflux of nitrite are fast compared to the rate of nitrite reduction (Bryan et al 1983).…”
Section: Enzyme-level Differencesmentioning
confidence: 99%
“…Previous studies have shown that variations in cellularlevel isotope effect expression is imparted by changes to the ratio of cellular substrate uptake to efflux (Shearer et al 1991;Needoba et al 2004;Granger et al 2008). However, it has been shown in P. stutzeri that uptake and efflux of nitrite are fast compared to the rate of nitrite reduction (Bryan et al 1983).…”
Section: Enzyme-level Differencesmentioning
confidence: 99%
“…In particular, noted that among monocultures of four phytoplankton strains, two diatoms and a prymnesiophyte showed higher N isotope effects in light-limited vs. high-light cultures, whereas one diatom species exhibited no increase in 15 ε at low light. Speciesspecific differences in 15 ε as well as intra-species differences in 15 ε have been attributed to variation in the expression of the enzymatic isotope effect imposed by nitrate reductase, which is determined by the ratio of NO − 3 effluxing out of the cell relative to its uptake (Shearer et al, 1991;Granger et al, 2004;. The intrinsic N (and O) isotope effect(s) of the eukaryotic assimilatory NO − 3 reductase in vitro has been estimated to be ∼27‰ (Karsh et al, 2012), whereas data on the N or O isotope effects imparted on NO − 3 during its active uptake at the cell surface indicate that they range between minor (up to 2‰; Karsh et al, 2013) and undetectable (Granger et al, 2010).…”
Section: Growth Dynamics At High and Low Lightmentioning
confidence: 99%
“…N and O isotope discrimination of NO − 3 during its assimilation is thus incurred dominantly during intracellular reduction by nitrate reductase. However, the enzymatic 15 N-enrichment that is transmitted to the external medium through cellular efflux of the internal NO − 3 pool and the cellular-level isotope effect (i.e., the expression of the isotope fractionation in the external medium) depends on the ratio of uptake to efflux (i.e., "efflux model"; Shearer et al, 1991;Granger et al, 2004;, which may vary with changing physiological and/or environmental conditions.…”
Section: Growth Dynamics At High and Low Lightmentioning
confidence: 99%
“…The efflux of NO − 3 from root to soil or the subsequent transport of NO − 3 within plants is not expected to discriminate 15 N as with the entry of soil NO − 3 into root cells (Mariotti et al, 1982; Shearer et al, 1991). This can be attributed to that the diffusion of NO − 3 through the membrane carriers of plant cells does not cause bonding breakage or consumption (Werner and Schmidt, 2002; Granger et al, 2004; Needoba et al, 2004).…”
Section: Isotopic Systematics Of No−3 In Plantsmentioning
confidence: 99%